Systematics of the frogs allocated to Sarcohyla bistincta sensu lato (Cope, 1877), with description of a new species from Western Mexico - Campbell, Jonathan A.; Brodie, Edmund D. Jr.; Caviedes-Solis, Itzue W.; de Oca, Adrián Nieto-Montes; Luja, Víctor H.; Flores-Villela, Oscar; García-Vázquez, Uri Omar; Sarker, Goutam Chandra; Wostl, Elijah; Smith, Eric N. (Zootaxa, 2018)
A new species of hylid frog is described from the southwestern edge of the Mexican Plateau from the states of Morelos and Mexico through Michoacán and Jalisco, reaching the Sierra Madre Occidental in Sinaloa and western Durango. The new species is part of the widespread Mexican hylid Sarcohyla bistincta (sensu amplo) complex, comprised of S. bistincta, S. pentheter, S. calthula, and S. ephemera. One subspecies of S. bistincta (labeculata) was proposed for an isolated population in Oaxaca. We restrict the group’s nominal species, S. bistincta (sensu stricto), to the Sierra Madre Oriental of Mexico and southward into the Sierra Madre del Sur of Guerrero and Oaxaca. Examination of type material places S. calthula and S. ephemera in the synonymy of S. labeculata (new combination). The species allied to S. bistincta, namely, S. bistincta, S. labeculata, S. pentheter, and the new species described herein, are diagnosed and described following recent suggested taxonomic changes and new available material.